1990
DOI: 10.1002/ffj.2730050105
|View full text |Cite
|
Sign up to set email alerts
|

Identification and sensory analysis of volatile constituents of babaco fruit (Carica pentagona heilborn)

Abstract: The volatile constituents of babaco fruit (Curicu penfagonu Heilborn) were investigated. Two different methods of isolation of the volatiles were employed: (a) reduced pressure steam distillation followed by dichloromethane extraction: (b) direct extraction of filtered babaco pulp with diethyl ether. HPLC fractionation of the extracts was carried out. The extracts were analysed by dual capillary gas chromatography and combined capillary GC-MS. The identified volatiles included 9 hydrocarbons, 20 alcohols, 9 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…It was reported as a component of a heated, but not unheated, mandarin juice . Similarly, it was observed in reduced pressure steam distillates of fresh babaco fruit, but not in diethyl ether extracts of fresh babaco pulp, and in reconstituted grapefruit concentrate, but not in fresh grapefruit juice . Damascenone was assessed as one of the most important volatile components of tomato paste samples in which it was found at an average concentration of 14 μg/kg, >10 times that in fresh tomatoes .…”
Section: Damascenone As a Natural Product And As A Component Of Foods...mentioning
confidence: 93%
“…It was reported as a component of a heated, but not unheated, mandarin juice . Similarly, it was observed in reduced pressure steam distillates of fresh babaco fruit, but not in diethyl ether extracts of fresh babaco pulp, and in reconstituted grapefruit concentrate, but not in fresh grapefruit juice . Damascenone was assessed as one of the most important volatile components of tomato paste samples in which it was found at an average concentration of 14 μg/kg, >10 times that in fresh tomatoes .…”
Section: Damascenone As a Natural Product And As A Component Of Foods...mentioning
confidence: 93%
“…Data treatment was performed using MSD ChemStation (E02.02) software, Agilent Technologies. The identification of compounds involved a comparison of mass spectra with those recorded by internal or commercial mass-spectral libraries (Flora, NIST and Wiley), as well as comparison of linear retention indices (LRI) with those available in the literature (NIST, ESO) and articles for data missing from databases mentioned above [ 2 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. Retention indices (RI) were calculated using a formula according to van Den Dool and Kratz [ 51 ] and according to the retention times of standard n-alkanes C6-C27 homemade mixture.…”
Section: Methodsmentioning
confidence: 99%
“…Shaw et al (1985) identified 32 chemical components in babaco fruit using gas chromatography (GC) and GC-mass spectroscopy (GC-MS) and suggested ethylbutanoate and ethyl hexanoate as important contributors to the unique flavor. Barbeni et al (1990) used GC and GC-MS to identify 9 hydrocarbons, 20 alcohols, 9 carbonyls, 9 acids, 60 esters, 3 lactones, 2 sulfur compounds, and 7 miscellaneous components in the fruit. They listed butan-1-ol and hexan-1-ol as the two major components, but suggested aroma and flavor were a collective effect of many compounds.…”
Section: Past and Present Researchmentioning
confidence: 99%